Z Score Reference Ranges of Fetal Cardiothoracic Diameter Ratio - Sirinart Sirilert (2019)
© 2018 by the American Institute of Ultrasound in Medicine Objective: This study aims to establish the z score reference ranges of cardiothoracic diameter ratio (CTR) of normal fetuses from 14 to 40 weeks’ gestation. Method: A cross-sectional study was conducted on low-risk singleton pregnancies with healthy fetuses. The CTR was performed using simple 2-dimensional sonography on the typical fetal 4-chamber view. The reference ranges were constructed according to gestational age (GA), biparietal diameter (BPD), and head circumference (HC) as independent variables based on the best-fit models, both mean and standard deviation (SD). Results: A total of 683 fetuses were measured for CTR. The best-fit equations for the mean and SD as a function of GA, BPD, and HC are as follows: (1) CTR = 0.365 + 0.004 × GA in weeks (SD = 0.031 + 0.001 × GA); (2) CTR = 0.373 + 0.014 × BPD in cm (SD = 0.034 + 0.004 × BPD); and (3) CTR = 0.373 + 0.004 × HC in cm (SD = 0.032 + 0.001 × HC). The CTR was slightly increased with advanced GA, BPD, and HC. Conclusion: Complete nomograms with z score reference ranges of CTR were established throughout pregnancy. These nomograms may be useful to detect cardiac abnormalities.